D4N2024 Presentation Showcase – Thematic Session 1b: Multisectoral approaches to improving maternal and child nutrition - Parvin, Aklima; Poudel, Sasmita; Thapa, Lila Bikram; Kumbhakar, Satyanarayan; Das, Pinaki; Bhandari, Jhabindra; Gogia, Keertana; Mridha, Malay Kanti; Mastan, Melinda; Das, Sushmita; Rajan, Sheetal; Poddar, Sukanya; et al. (International Food Policy Research Institute, 2024)
Oral presentations: Connecting the Dots Between Agriculture, Nutrition, and Health to Improve Nutrition-Sensitive Agriculture: A Government-Led Randomized Controlled Trial in Rural Bangladesh Aklima Parvin, Senior Project Manager, International Food Policy Research Institute